Study of 14-3-3 η eta protein in juvenile idiopathic arthritis - Khaled Omar Elfarouk Zaiton; Yasser Abd-Elaziz Abd-Elhamid; Nashwa Ismail Hashaad; Inas A Ahmed; Noha Hosni Ibrahim (Egyptian Rheumatology and Rehabilitation)
Abstract Background Juvenile idiopathic arthritis (JIA) refers to all types of arthritis that begin before the age of 16 and last more than 6 weeks, with no known cause. The 14-3-3 η eta protein is a new biomarker linked to the development of rheumatoid arthritis and joint destruction. We sought to evaluate the 14-3-3 η eta protein’s potential as a diagnostic biomarker for JIA and its correlation with both functional outcome and disease activity. Results Significant levels of 14-3-3 η eta protein were found in rheumatoid factor (RF)-positive polyarticular JIA and RF-negative polyarticular JIA patients. Enthesitis-related arthritis (ERA) is associated with the lowest value of 14-3-3 η eta. 14-3-3 eta protein was significantly positively linked with CHAQ and JADAS 27 (p = 0.008 & 0.001, respectively). Conclusion The 14-3-3 η eta protein could be used as a biomarker to diagnose and monitor JIA. Significant levels of 14-3-3 η eta protein can be found in RF-positive polyarticular JIA and RF-negative polyarticular JIA patients. The 14-3-3 η eta protein correlates positively with disease activity and functional outcome in JIA.